Growing‐season warming and winter soil freeze/thaw cycles increase transpiration in a northern hardwood forest. Issue 11 (22nd September 2020) - Harrison, Jamie L.; Sanders‐DeMott, Rebecca; Reinmann, Andrew B.; Sorensen, Patrick O.; Phillips, Nathan G.; Templer, Pamela H.
Abstract: Climate models project higher growing‐season temperatures and a decline in the depth and duration of winter snowpack throughout many north temperate ecosystems over the next century. A smaller snowpack is projected to induce more frequent soil freeze/thaw cycles in winter in northern hardwood forests of the northeastern United States. We measured the combined effects of warmer growing‐season soil temperatures and increased winter freeze/thaw cycles on rates of leaf‐level photosynthesis and transpiration (sap flow) of red maple ( Acer rubrum ) trees in a northern hardwood forest at the Climate Change Across Seasons Experiment at Hubbard Brook Experimental Forest in New Hampshire. Soil temperatures were warmed 5°C above ambient temperatures during the growing season and soil freeze/thaw cycles were induced in winter to mimic the projected changes in soil temperature over the next century. Relative to reference plots, growing‐season soil warming increased rates of leaf‐level photosynthesis by up to 85.32 ± 4.33%, but these gains were completely offset by soil freeze/thaw cycles in winter, suggesting that increased freeze/thaw cycles in winter over the next 100 yr will reduce the effect of warming on leaf‐level carbon gains. Soil warming in the growing season increased rates of transpiration per kilopascal of vapor pressure deficit (VPD) by up to 727.39 ± 0.28%, even when trees were exposed to increased frequency of soil freeze/thaw cycles in the previous winter, which could influence regional hydrology in the future. Using climate projections downscaled from the Coupled Model Intercomparison Project, we project increased rates of whole‐season transpiration in these forests over the next century by 42–61%. We also project 52–77 additional days when daily air temperatures will be above the long‐term average daily maximum during the growing season at Hubbard Brook. Together, these results show that projected changes in climate across both the growing season and winter are likely to cause greater rates of water uptake and have no effect on rates of leaf‐level carbon uptake by trees, with potential ecosystem consequences for hydrology and carbon cycling in northern hardwood forests.